PLATFORM-BASED BUSINESS DEVELOPMENT STRATEGY: INCREASING CUSTOMER ENGAGEMENT AND COMPETITIVE ADVANTAGE IN SMEs - Muh. Husriadi; Muhammad Aswin; La Ode Wahidin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The aim of this research is to determine the factors that influence the continuity of micro, small and medium enterprises (MSMEs) in Kendali. Using a cross-sectional survey, we analyze access to capital, supporting infrastructure, and digital technology adoption as independent variables. The analysis shows that access to capital, supporting infrastructure, and the application of digital technology have a significant impact on MSMEs operations and sustainability. These findings show the importance of developing policies that support access to capital and supporting infrastructure, as well as increasing awareness among SMEs of the importance of adopting digital technology to increase the competitiveness and sustainability of their businesses. Realizing this impact, it is hoped that small, medium and micro businesses in Kendari City can develop sustainably and contribute more to regional economic growth.